Monsoonal forcing of cold-water coral growth off southeastern Brazil during the past 160 kyr - Bahr, André; Doubrawa, Monika; Titschack, Jürgen; Austermann, Gregor; Koutsodendris, Andreas; Nürnberg, Dirk; Albuquerque, Ana Luiza; Friedrich, Oliver; Raddatz, Jacek (Biogeosciences, 2020)
Abstract. Cold-water corals (CWCs) constitute important deep-water ecosystems that are under increasing environmental pressure due to ocean acidification and global warming. The sensitivity of these deep-water ecosystems to environmental change is demonstrated by abundant paleorecords drilled through CWC mounds that reveal characteristic alterations between rapid formation and dormant or erosive phases. Previous studies have identified several central parameters for driving or inhibiting CWC growth such as food supply, oxygenation, and the carbon saturation state of bottom water, yet there are still large uncertainties about the relative importance of the different environmental parameters. To advance this debate we have performed a multiproxy study on a sediment core retrieved from the 25 m high Bowie Mound, located at 866 m water depth on the continental slope off southeastern Brazil, a structure built up mainly by the CWC Solenosmilia variabilis. Our results indicate a multifactorial control on CWC growth at Bowie Mound during the past ∼160kyr, which reveals distinct formation pulses during northern high-latitude glacial cold events (Heinrich stadials, HSs) largely associated with anomalously strong monsoonal rainfall over the continent. The ensuing enhanced runoff elevated the terrigenous nutrient and organic-matter supply to the continental margin and likely boosted marine productivity. The dispersal of food particles towards the CWC colonies during HSs was facilitated by the highly dynamic hydraulic conditions along the continental slope that prevailed throughout glacial periods. These conditions caused the emplacement of a pronounced nepheloid layer above Bowie Mound, thereby aiding the concentration and along-slope dispersal of organic matter. Our study thus emphasizes the impact of continental climate variability on a highly vulnerable deep-marine ecosystem.